Microstructure Characterization of Bone Metastases from Prostate Cancer with Diffusion MRI: Preliminary Findings - Bailey, Colleen; Collins, David J.; Tunariu, Nina; Orton, Matthew R.; Morgan, Veronica A.; Feiweier, Thorsten; Hawkes, David J.; Leach, Martin O.; Alexander, Daniel C.; Panagiotaki, Eleftheria (Frontiers in Oncology, 2018)
PURPOSE: To examine the usefulness of rich diffusion protocols with high b-values and varying diffusion time for probing microstructure in bone metastases. Analysis techniques including biophysical and mathematical models were compared with the clinically-used apparent diffusion coefficient (ADC). METHODS: Four patients were scanned using 13 b-values up to 3000 s/mm2 and diffusion times ranging 18 to 52 ms. Data were fitted to mono-exponential ADC, intravoxel incoherent motion (IVIM), Kurtosis and VERDICT models. Parameters from the models were compared using correlation plots. RESULTS: ADC and IVIM did not fit the data well, failing to capture the signal at high b-values. The Kurtosis model best explained the data in many voxels, but in voxels exhibiting a more time-dependent signal, the VERDICT model explained the data best. The ADC correlated significantly (p<0.004) with the intracellular diffusion coefficient (r=0.48), intracellular volume fraction (r=-0.21) and perfusion fraction (r=0.46) parameters from VERDICT, suggesting that these factors all contribute to ADC contrast. The mean kurtosis correlated with the intracellular volume fraction parameter (r=0.26) from VERDICT, consistent with the hypothesis that kurtosis relates to cellularity, but also correlated weakly with the intracellular diffusion coefficient (r=0.18) and cell radius (r=0.16) parameters, suggesting that it may be difficult to attribute physical meaning to kurtosis. CONCLUSION: Both Kurtosis and VERDICT explained the diffusion signal better than ADC and IVIM, primarily due to poor fitting at high b-values in the latter two models. The Kurtosis and VERDICT models captured information at high b using parameters (Kurtosis or intracellular volume fraction and radius) that do not have a simple relationship with ADC and that may provide additional microstructural information in bone metastases.